PENGARUH DUKUNGAN PEMILIK, KEMAMPUAN TEKNIK PERSONAL, PROGRAM PELATIHAN DAN PENDIDIKAN TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI (Survei pada Usaha Kecil dan Menengah Kerajinan Logam Dusun Tumang Desa Cepogo) - Arantio, Yosua Reno; Sarwono, Aris Eddy; Puji Astuti, Dewi Saptantinah (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
This study aims to determine the effect of owner support, personaltechnical skills, training and education programs on the performance ofaccounting information systems. This research was conducted at Small andMedium Enterprises (SMEs) of Metal Crafts in Tumang Hamlet, Cepogo Village.The type of data used is quantitative data. The data source used is primary data.The data collection technique used a questionnaire. The population used in thisstudy were 212 Metal Craft UKM in Tumang Hamlet, Cepogo Village. The sampleused in this study is 46 SMEs that have used SIA and from 46 SMEs tworespondents are taken, namely the owner and the finance and or administrationdepartment. The sampling technique was purposive sampling method. This studyshows that owner support, personal technical skills, training and educationprograms affect the performance of the accounting information system.